Generation of Neutrophil Mediators During an Experimental Infection with Rhinovirus-16 in Asthmatic Patients - Sullivan, Robert A.; Rajadhyaksha, Evan; Jorge, Patricia; Carper, Holliday T.; Murphy, Deborah D.; Platts-Mills, Thomas A.E.; Heymann, Peter W. (Journal of allergy and clinical immunology, 2018)
Cumulative values (summed over days 1-3 following RV inoculation) trended higher in asthmatics compared to controls (e.g., geometric means for NE=3775ng/mL and 2167ng/mL, respectively, p=0.45; MPO=1375ng/mL and 917.3ng/mL, p=0.66), but this trend was not apparent during resolution of the infection (days 14 and 21). Conclusions During the early (innate) phase of the infection, a consistent trend in higher levels of neutrophil mediators was observed in nasal washes from asthmatic subjects compared to controls.